Co/N-doped carbon nanospheres derived from an adenine-based metal organic framework enabled high-efficiency electrocatalytic nitrate reduction to ammonia. Issue 97 (17th November 2022) - Chen, Jie; Gong, Tao; Hou, Qian; Li, Jun; Zhang, Longcheng; Zhao, Donglin; Luo, Yongsong; Zheng, Dongdong; Li, Tingshuai; Sun, Shengjun; Cai, Zhengwei; Liu, Qian; et al.
Abstract : Co/N-doped carbon nanospheres act as a superb catalyst for ambient NH3 synthesis via electrochemical NO3 − reduction, attaining a large NH3 yield of 758.0 μmol h −1 mgcat. −1 and a high faradaic efficiency of up to 96.5%. Abstract : Electrocatalytic nitrate (NO3 − ) reduction provides us a dual-function strategy for N-contaminant removal and value-added ammonia (NH3 ) synthesis. However, there is still a lack of efficient electrocatalysts for selective NO3 − reduction. Herein, we report the development of Co/N-doped carbon nanospheres derived from an adenine-based metal organic framework (Co@NC) as an attractive electrocatalyst for efficient NH3 synthesis through the reduction of NO3 − . Such Co@NC manifests a notable faradaic efficiency of 96.5% and a high NH3 yield of up to 758.0 μmol h −1 mgcat. −1 in 0.1 M NO3 − -containing 0.1 M NaOH. Moreover, it also demonstrates strong electrochemical stability.